A Concise Synthesis of (−)‐Incrustoporin and its Analogues by Pd–catalyzed Suzuki‐Miyaura Coupling from γ‐Vinyl‐γ‐butyrolactone. Issue 16 (7th October 2016) - Nallasivam, Jothi L.; Fernandes, Rodney A.
Abstract: A highly efficient synthesis of C3‐arylbutenolides by Suzuki‐Miyaura coupling is described. We developed a simple protocol to accomplish scaffolds of C3‐arylbutenolides which include antifungal agent (−)‐incrustoporin and twelve analogues by Pd‐catalyzed Suzuki‐Miyaura cross coupling reaction between chiral 3‐iodobutenolide and various aryl boronic acids under aerobic conditions in good to quantitative yields. Abstract : A highly efficient synthesis of C3‐arylbutenolides via Suzuki‐Miyaura coupling is described. We developed a simple protocol to accomplish scaffolds of C3‐arylbutenolides which include antifungal agent (−)‐incrustoporin and twelve analogues by Pd‐catalyzed Suzuki‐Miyaura cross coupling reaction between chiral 3‐iodobutenolide and various aryl boronic acids under aerobic conditions in good to quantitative yields.